The Impact of Social Media on Pragmatic Understanding Among Students - Dianti, Hilmina Rahma; Putri, Intan Cahyani (Reflection Journal, 2024)
This study aims to explore how social media affects the pragmatic comprehension of students at the University of Muhammadiyah Tangerang (UMT). Specifically, it investigates how platforms like Instagram, WhatsApp, Telegram, and TikTok influence students' ability to use language proficiently in diverse social contexts. The research employed qualitative methods, including in-depth interviews and questionnaires administered to 17 students in the English education program at UMT. The study found that 47.1% of respondents strongly agreed that social media positively impacts their pragmatic knowledge, while 41.2% agreed, indicating a general consensus on its benefits. Additionally, 76% of students reported that engaging in social media interactions heightened their awareness of socio-pragmatic norms, and 72% found their language learning experiences more interactive and engaging due to social media. These findings suggest that social media platforms can enhance pragmatic skills through informal and diverse language interactions. The study concludes by advocating for the incorporation of social media into language education to bridge the gap between formal education and real-world communication, thereby improving overall learning and pragmatic competence